Answer:
first piece = 1.88in
second piece= 3.76in
third piece = 26.32in
32 = f + s + t
1st piece = f
2nd piece = s
3rd piece = t
what we know:
s = 2f
t = 2(7f)
32 = f + 2f + 2(7f)
32 = 3f +14f
32 = 17f
f = 1.88
now sub in:
f = 1.88
s = 3.76
t = 26.32
when you add these together you get 31.96, when you round up you get 32 which is the original piece of steel.
Answer:
a . See attachment
b. because we will find the distance from the bottom of the ladder to the base of the building.
c. sin 60 = opposite side / hypotenuse
d.sin 60 = x / 10
e . 8.66 ft =x
f. see attachment
i. cos 60° = adjacent side / hypotenuse
Step-by-step explanation:
a . See attachment
b. because cos 60° = adjacent side / hypotenuse, the hypotenuse is equal to the length of the ladder (10), and the adjacent side that we will find is the distance from the bottom of the ladder to the base of the building. not the height that the ladder reaches .
c. sin 60 = opposite side / hypotenuse
Because we will find the opposite side which is the height that the ladder reaches.
d.sin 60 = x / 10
e .
0.866025403 = x/10
10 (0.866025403) =x
8.66 ft =x
f. see attachment
i. cos 60° = adjacent side / hypotenuse
Because we will find the adjacent side which is the distance from the bottom of the ladder to the base of the building.
Answer:
2
Step-by-step explanation:
-4x -y + 4
=-4*-1/4 -3 + 4
=1+1
=2
Answer:
55.56%
Step-by-step explanation:
= (20 / 36) × 100
= 0.56 × 100
= 55.56%
Answer:
60 feet
Step-by-step explanation:
a - 2x
b - x
c - 3x
120/6 = 20
20 x 3 = 60